Sonic Hedgehog Signaling in Cranial Neural Crest Cells Regulates Microvascular Morphogenesis in Facial Development - Sun, Miranda R.; Chung, Hannah M.; Matsuk, Veronika; Fink, Dustin M.; Stebbins, Matthew J.; Palecek, Sean P.; Shusta, Eric V.; Lipinski, Robert J. (Frontiers in Cell and Developmental Biology, 2020)
Sonic hedgehog (Shh) pathway disruption causes craniofacial malformations including orofacial clefts of the lip and palate. In normal craniofacial morphogenesis, Shh signals to multipotent cranial neural crest cells (cNCCs) and was recently discovered to regulate the angiogenic transcriptome, including expression markers of perivascular cells and pericytes. The mural cells of microvasculature, pericytes in the brain and face differentiate from cNCCs, but their role in facial development is not known. Here, we examined microvascular morphogenesis in a mouse model of Shh pathway antagonist-induced cleft lip and the impact of cNCC-specific Shh pathway activation in a cNCC-endothelial cell coculture system. During cleft pathogenesis in vivo, disrupted microvascular morphogenesis localized with attenuated tissue outgrowth in the medial nasal processes that form the upper lip. In vitro, we found that human umbilical vein endothelial cell cord formation was not affected by direct Shh pathway perturbation. However, in a coculture system in which cNCCs directly interact with endothelial cells, cNCC-autonomous Shh pathway activity significantly prolonged endothelial cord network stability. Taken together, these findings support the premise that Shh pathway activation in cNCCs promotes pericyte-like function and microvascular stability. In addition to suggesting a previously unrecognized role for Shh signaling in facial development, these studies also identify perivascular differentiation and microvascular morphogenesis as new focuses for understanding normal and abnormal craniofacial development.